STUDI ANALISIS PERSYARATAN KEBUTUHAN SISTEM DALAM MENGHASILKAN PERANGKAT LUNAK YANG BERKUALITAS - Sandy Kosasi; Susanti Margaretha Kuway (SISFOTENIKA, 2012)
Abstracts: Requirements specification is the need for the early phases of software engineering and is very important because it affects the flexibility, reliability, accuracy and usability. No matter how good coding and design systems that do not will still be able to provide a real desire by the conditions encountered. In fact, the needs for requirements engineering and FAST approach method does not always ensure produce quality software systems so that require system migration. In this process the need for requirements analysis should also consider factors that can not be empirically expressed quantitatively. Further requires adaptability and develop alternative priority needs in terms of the requirements document. Communication skills, the use of simple terms, open to users of the system, and displays a vivid example of what is needed and avoid the pitfalls of the intelligence domain to limit the success factors in aligning with the expectations of users of the system.Keywords : requirements specification analysis, requirements engineering, FAST approach, system migration, quantitative and empirical pitfalls intelligence domain.